Technology-Enhanced Vs. Traditional Approaches To Pediatric Nutrition Education: A Comparative Analysis - Nurwati, Yuni (Journal of Engineering Science and Technology Management, 2025)
The digital transformation in education has introduced innovative approaches to paediatric nutrition education, offering alternatives to traditional methods. This comparative analysis examined the effectiveness of technology-enhanced versus traditional approaches in improving nutritional knowledge and behaviour among Indonesian children and adolescents. The aimed of this review was to systematically compare the effectiveness of technology-enhanced and traditional approaches to paediatric nutrition education based on primary research studies conducted in Indonesia. This review analyzed ten primary research studies conducted in Indonesia between 2015-2025, examining various educational intervention including digital media (videos, mobile applications, social media), interactive games, and traditional methods (leaflets, face-to-face counselling) across different paediatric populations. Technology-enhanced interventions demonstrated superior effectiveness compared to traditional methods. Digital interventions showed knowledge improvement rates ranging from 19.5% to 73.3%, while traditional methods achieved 8.2% to 12.6% improvement. Video-based education proved most effective (mean improvement: 27.39 points), followed by mobile applications (68% to 87.3% correct response) and social media platforms. In conclusion, technology-enhanced approaches to paediatric nutrition education significantly outperformed traditional methods in improving nutritional knowledge and attitudes among Indonesian children and adolescents, with video-based interventions showing the highest efficacy.